AVALIAÇÃO DA EFICÁCIA DAS CAIXAS DE CONTENÇÃO DE SEDIMENTO EM ESTRADAS RURAIS NÃO PAVIMENTADAS NA BACIA DO RIO DAS PEDRAS, GUARAPUAVA-PR - Cunha, Márcia Cristina da (2012)
The layout of the roads that cross numerous rivers, added with lateral drainage causes the water to come quickly to the drainage network by increasing the flow. This results in high sediment yield considering that some internal roads and paths have no sinks of energy. Therefore this study aimed to examine and discuss the evaluation of containment boxes effectiveness as a measure sediment control on rural roads of Sones River basin, Guarapuava, Paraná, Brazil, as well as to measure the characteristics of the roads in this area. In this study we used the manipulation of available data in a digital middle, performed in the field with interviews, collection of precipitation data, flow and turbidity measurement and 1996-2009 series of country roads. By analyzing the results it was found that much of the Stones River basin still has significant coverage, i.e around 90.1% of the area is still covered with vegetation, however the use of land involves diversified activities such as agriculture, industry, livestock and others. The basin drainage system is the fifth order with drainage density of 1.37 km / km ?, characterizing it as of poor drainage. The number of internal paths overcomes the main roads, which largely lacks energy sink, increasing the input of sediment in rivers. The basin has slopes between 80-20% in 44% of the area indicating Plains. It was found that around 70% of measured boxes were inactive, with a deterioration in average 10% of cases measured every two years. In the studied series that includes 14 years (1996-2009), it was found that there was a turbidity reduction of 21.5% after the implementation of sediment control measures. Data analysis showed that the turbidity decreased significantly after the implementation of the boxes, also reducing the cost of water treatment that supplies the city, however as there was no maintenance, the containment boxes were gradually losing their effectiveness.